A Systematic Review of Interventions to Increase Physical Activity Among American Indian and Alaska Native Older Adults. (19th February 2021) - Pedersen, Maja; Harris, Kari Jo; Brown, Blakely; Anderson, Keith; Lewis, Jordan P
Abstract: Background and Objectives: Physical activity (PA) is a powerful protective factor known to reduce risk for chronic conditions across the life span. PA levels are lower among American Indians and Alaska Natives (AIANs) when compared with other racial/ethnic groups and decrease with age. This evidence justifies a synthesis of current intervention research to increase PA levels among AIANs. This systematic review examines completed interventions to increase PA among AIAN older adults and considers recommended practices for research with Indigenous communities. Research Design and Methods: The systematic review was designed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement for systematic review protocols and reporting guidelines. Three electronic databases, PubMed, Web of Science, and PsycINFO, were searched for academic literature. Trials investigating interventions to increase PA among AIAN adults older than 50 years were eligible. The Quality Assessment Tool for Quantitative Studies was used to evaluate the quality of evidence. Results: Three published trials were identified, including one group-level, clinic-based and two individual-level, home-based interventions. All were 6 weeks in duration, took place in urban areas, and used self-report PA measures. Findings indicated an overall increase in PA levels, improved PA-related outcomes, and improved psychosocial health among participants. None described community-engaged or culture-centered research strategies. Discussion and Implications: The narrow yet promising evidence represents a need for expanded research and a call to action for using culture-centered strategies. An advanced understanding of cultural and contextual aspects of PA may produce more impactful interventions, supporting health and mobility across the life span.